2019
DOI: 10.1016/j.carpath.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathological correlates of brain arterial calcifications

Abstract: Background: In clinical practice, calcifications seen on CT studies within the large brain arteries are often referred as a surrogate marker for cholesterol-mediated atherosclerosis. However, limited data exists to support the association between calcification and atherosclerosis. In this study, we examined if intracranial arterial calcifications were associated with cholesterol-mediated intracranial large artery atherosclerosis (ILAA) within the arteries of the Circle of Willis in an autopsy based sample. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Priors studies have demonstrated that compared with the deep, coalescent calcification, superficial and scattered calcification was more associated with plaque instability (41,42). Furthermore, some scattered micro-calcifications that may be more related to culprit plaques (43) are beyond the resolution of a CT scan (44), which may lead to an underestimation of the prevalence of calcification in plaques. Lastly, since IAC is more prevalent in Asians, African Americans, and Hispanics than in Caucasians (20,26), larger studies involving other populations are needed to increase the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Priors studies have demonstrated that compared with the deep, coalescent calcification, superficial and scattered calcification was more associated with plaque instability (41,42). Furthermore, some scattered micro-calcifications that may be more related to culprit plaques (43) are beyond the resolution of a CT scan (44), which may lead to an underestimation of the prevalence of calcification in plaques. Lastly, since IAC is more prevalent in Asians, African Americans, and Hispanics than in Caucasians (20,26), larger studies involving other populations are needed to increase the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although ICAD can be diagnosed with noninvasive imaging techniques like transcranial doppler and MRA, the gold standard for the diagnosis is DSA. (12,13,14,15) Autopsy studies are limited on ICAD and suggest that scattered calci cations (microscopic) are associated with cholesterol mediated intracranial large artery atherosclerosis, and stenosis as opposed to coalescent (macroscopic) calci cations (16). Another study concluded that only intimal calci cation as opposed to internal elastic lamina and adventitial calci cation was associated with ICAD.…”
Section: Discussionmentioning
confidence: 99%
“…They found that intimal calcification, medial calcification, and severity of calcification in IICA were all associated with stroke ( Golüke et al, 2020 ). Recently, a histopathology study of 211 autopsy cases also revealed that the presence of calcification in the circle of Willis was associated with ischemic infarcts ( Shapiro et al, 2019 ). Combined together, these results substantiated an association between IAC and the risk of stroke.…”
Section: Intracranial Artery Calcificationmentioning
confidence: 99%
“…Recently, a histopathological study categorized calcifications in the circle of Willis into large calcifications (“coalescent”), which can be detected on CT, and small calcifications (“scattered”), which are likely undetectable on CT. They found that small calcifications were associated with cholesterol-driven intracranial large artery atherosclerosis while large calcifications were not associated with atherosclerosis ( Shapiro et al, 2019 ). Small calcification, or microcalcification, is not merely a process induced by atherosclerotic inflammation but it can also elicit a pro-inflammatory response in macrophages ( Nadra et al, 2005 ).…”
Section: Intracranial Artery Calcificationmentioning
confidence: 99%